Estimation of the conicity of the root canals of the first inferior primary molars, using Nano computerized tomography (Nano-CT): In vitro study - Torres - Ramos, Gilmer (2020)
Objectives: Estimate the root canals of primary first lower molars by means of Nano computed tomography (Nano-CT). Material and methods: The sample consisted of 10 inferior primary molar teeth. The teeth were scanned by Nano-CT and the resulting images were analyzed with the On-Demand 3D software, considering among the evaluation the anatomical characteristics of the root canals and surface area of the root canals throughout the root length. For the measurement of the larger and smaller diameter of the root canals the statistical tests were central trend measures, with a significance level of 5%.  Results: In the distal root, vestibular mesial and lingual mesial , the size of the root canal with the highest average of the cervical region (D0) was 1.30, 1.00, 1.08 mm, respectively. The diameter to the deepest length (D11) for the same canals was 0.29, 0.22, 0.18 mm. The measurement of the distal root surface area, vestibular mesial and lingual mesial in the cervical line (D0) was 1.43,0.87, 1.01 mm. The area at the deepest length (D11) was 0.09, 0.04, 0.03mm2.  Conclusions: The morphology of the roots and root canals of the first primary molars had a conical distribution being their diameters and larger areas in the cervical region and decrease in the apical region.